2012
DOI: 10.1016/j.neuron.2011.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Otic Mesenchyme Cells Regulate Spiral Ganglion Axon Fasciculation through a Pou3f4/EphA4 Signaling Pathway

Abstract: SUMMARY Peripheral axons from auditory spiral ganglion neurons (SGNs) form an elaborate series of radially and spirally oriented projections that interpret complex aspects of the auditory environment. However, the developmental processes that shape these axon tracts are largely unknown. Radial bundles are comprised of dense SGN fascicles that project through otic mesenchyme to form synapses within the cochlea. Here, we show that radial bundle fasciculation and synapse formation are disrupted when Pou3f4 (DFNX2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 59 publications
9
115
2
Order By: Relevance
“…This model is compatible with recent data showing that, during the anterior stage of fibre outgrowth and extension to the OC, EphA4 is expressed in the otic mesenchyme and interacts with ephrin-B2 on developing SGN axons 25 . Indeed, it can be suggested that, at late embryonic stages, EphA4 promotes SGN fasciculation through ephrin-B2 reverse signalling; once afferents have reached the OC, EphA4 (expressed in type I SGNs) forward signalling controls target specification through interaction with ephrin-A5 (expressed by OHCs) at early postnatal stages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This model is compatible with recent data showing that, during the anterior stage of fibre outgrowth and extension to the OC, EphA4 is expressed in the otic mesenchyme and interacts with ephrin-B2 on developing SGN axons 25 . Indeed, it can be suggested that, at late embryonic stages, EphA4 promotes SGN fasciculation through ephrin-B2 reverse signalling; once afferents have reached the OC, EphA4 (expressed in type I SGNs) forward signalling controls target specification through interaction with ephrin-A5 (expressed by OHCs) at early postnatal stages.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, it can be suggested that, at late embryonic stages, EphA4 promotes SGN fasciculation through ephrin-B2 reverse signalling; once afferents have reached the OC, EphA4 (expressed in type I SGNs) forward signalling controls target specification through interaction with ephrin-A5 (expressed by OHCs) at early postnatal stages. Importantly, this hypothesis of a double role for EphA4 is supported by the fact that, in addition to be expressed in the otic mesenchyme, EphA4 mRNA was also found in the SG 25 .…”
Section: Discussionmentioning
confidence: 90%
“…Each bundle is formed of fibers with similar frequency tuning. This distinct fasciculation pattern is more evident at the base/mid region of the cochlea than at the apex (17). SGN axons in Ror1 mutant cochlea failed to fasciculate correctly, arranging in less condensed bundles (Fig.…”
Section: Auditory Neuropathy and Inner Ear Anatomic Defects In Ror1 Mmentioning
confidence: 92%
“…To investigate the effect of Ror1 deficiency on the neuronal phenotype within the organ of Corti, we analyzed the total innervation pattern (z-stack images) in P5 whole-mount surface preparations of cochlea labeled with anti-neurofilament antibody and counterstained with phalloidin. In cochlear development, spiral ganglion neurons (SGNs) project peripheral axons through surrounding mesenchyme cells, forming dense fascicles before penetrating the sensory epithelium (17). Each bundle is formed of fibers with similar frequency tuning.…”
Section: Auditory Neuropathy and Inner Ear Anatomic Defects In Ror1 Mmentioning
confidence: 99%
See 1 more Smart Citation